FACTORS ASSOCIATED WITH OBESITY AND ABDOMINAL OBESITY AMONG INHABITANTS IN ONGKHARAK SUBDISTRICT, ONGKHARAK DISTRICT, NAKHONNAYOK PROVINCE - Chuemongkon, Wannakon; Nakwikrai, Jitdapha; Sarataiakom, Thanyachanok (Srinakharinwirot University Journal of Sciences and Technology, 2023)
Obesity and abdominal obesity are predominant risk factors for the development of non-communicable diseases (NCDs) which are public health concern and also socioeconomic problems in Thailand and worldwide. This survey study aimed to assess the prevalence and associated factors of obesity and abdominal obesity among inhabitants in Ongkharak subdistrict, Ongkharak district, Nakhonnayok province in 356 participants. Data were collected by using questionnaires including general data, individual behaviors, and stress levels. Obesity and abdominal obesity were evaluated by the body mass index (BMI) and waist circumference, respectively. The results showed that most participants were female (57.87%) and mild stress level (45.79%). The average age, BMI and waist circumference were 38.94 years, 24.69 kilograms per square meters and 85.48 centimeters, respectively. The prevalence of obesity and abdominal obesity were 42.98% and 50.28%, respectively. Factors significantly associated obesity were occupation, income, hypertension and dyslipidemia. Factors significantly related abdominal obesity were gender, age, marital status, hypertension and dyslipidemia. These lead to the development of educating guidelines for individuals to take care of themselves. The properly change in their behavior and lifestyle, especially controlling of blood pressure and blood lipid may improve obesity, abdominal obesity and consequential NCDs.